Pilot Study on Nucleation-Induced Pelleting Coagulation in Treatment of High-Algae Surface Water: Coagulant Dosage and Hydraulic Loading Optimization - Xiangxuan Xing; Tinglin Huang; Ruizhu Hu; Kai Li (Toxics)
This study proposes a circulating pelletized fluidized bed (CPFB) with micro-sand loading for treating high-algae surface water. Key operational parameters (coagulant dosage, flow rate) were optimized to simultaneously remove algae, turbidity, and disinfection byproduct precursors. Results revealed that 20 mg/L polyaluminum chloride (PACl) and 0.8 mg/L PAM achieved optimal removal of algae (density removal > 80%) and organic matter. The fluidized bed exhibited robust performance across algal species, with the highest dichloroacetonitrile (DCAN) precursor removal of 66.20%, demonstrating superior efficiency for trihalomethane precursors over haloacetic acids. These findings provide critical operational guidance for high-algae water treatment using fluidized beds.